PENGARUH POSISI PRONASI TERHADAP STATUS HEMODINAMIK ANAK YANG MENGGUNAKAN VENTILASI MEKANIK DI RUANG PEDIATRIC INTENSIVE CARE UNIT (PICU) RSAB HARAPAN KITA JAKARTA* - ORPA DIANA SUEK (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
One of therapeutic interventions to children receiving mechanical ventilation is pronation position that is aimed to improve the distribution of ventilation and reduce shunt intrapulmonary. The purpose of this study is to determine the effect of pronation position on the hemodynamic status of pediatric in the Pediatric Intensive Care Unit with 15 sample. The study used quasi experiment one-group pretest-posttest design. Measurement of hemodynamic status used the observation sheet to assess the respiratory rate, oxygen saturation, blood pressure, mean arterial pressure, and heart rate. The results of bivariate analysis were significant differences between oxygen saturation before and after the intervention with p value of 0.004 (p < 0.005, α: 0.05). In conclusion, pronation position effectively increases oxygen saturation.